AlN/3C-SiC composite plate enabling high-frequency and high-Q micromechanical resonators - Lin, Chih-Ming (Advanced materials (Deerfield Beach, Fla.), 2012)
Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.